Reduced Preoperative Glomerular Filtration Rate Is Associated With Adverse Postoperative Oncological Prognosis in Patients Undergoing Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma: A Retrospective Cohort Study - Li, Shijie; Chen, Xiaonan; Zheng, Jianyi; Liu, Xuefeng (Frontiers in Surgery, 2022)
Objective: To evaluate the association between perioperative estimated glomerular filtration rate (eGFR) and postoperative oncological outcomes in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU)，and to evaluate the effect of sex on this association. Methods: The medical records of patients with UTUC who underwent RNU between January 2012 and December 2017 at our hospital were retrospectively reviewed. Patients were divided into three groups based on preoperative eGFRs: normal eGFR (>60 mL/min/1.73 m2; n = 179), moderately reduced eGFR (45–60 mL/min/1.73 m2; n = 45), and severely reduced eGFR (≤45 mL/min/1.73 m2; n = 36). Statistical analyses were performed to evaluate the prognostic impact of preoperative eGFR on prognosis. Results: Patient mean age was 66.7 ± 9.6 years, and 47.9% were female. Multivariate regression analysis based on Cox proportional risk models and Kaplan-Meier survival rates showed that lower preoperative eGFR was associated with decreased OS, PFS, and CSS. In the adjusted Cox regression model, patients with normal and moderately reduced eGFRs had a decreased hazard for mortality, with adjusted hazard ratios of 0.13 (95% confidence interval [CI]: 0.07–0.26) and 0.36 (95% CI: 0.18–0.73), respectively (P < 0.001). The smooth fitting curve suggested a linear relationship between eGFR and prognostic survival. Additionally, sensitivity subgroup analyses verified an inverse relationship between the reduced eGFR and OS. Women had a lower eGFR and worse oncological outcomes than men. A nomogram for OS was developed based on multivariate analysis with a C-index of 0.754 (95% CI: 0.728–0.779). Conclusions: Preoperative renal insufficiency is strongly associated with a higher risk of cancer progression and a lower survival probability. It is important to identify preoperative renal insufficiency in patients with UTUC, particularly female patients.